Wet coffee processing discharges affecting quality of river water at Kayanza ecological zone, Burundi - Bisekwa, E.; Njogu, P.M.; Kufa Obso, T. (Scientific Research Publishing, Inc., 2021)
Wet coffee processing leads to the generation of large volumes of wastewater, whose discharge to the environment leads to pollution of freshwater bodies. Kayanza is a major coffee growing area in Burundi with more than 40 wet coffee processing factories (WCPF) that discharge effluents directly to receiving water bodies without treatment. This study was carried out to assess the effect of coffee wastewater on the physicochemical properties of receiving waterbodies in Kayanza coffee growing ecological zone. Currently, no study has been done to analyze the effluent from the WCPF and assess the level of pollution. This study will therefore provide valuable data on the water pollution from coffee processing plants. Ten (10) rivers in the Kayanza coffee growing zone were studied during the months of April and June, 2020. Water samples were collected upstream (U) and downstream (D) of the effluent discharge points in triplicate. Samples were analyzed for pH, Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD5), Temperature, Salinity, Electrical Conductivity (EC), Total Dissolved Solids (TDS), Dissolved Oxygen (DO), Total Suspended Solids (TSS), Nitrates, Nitrites, Lead (Pb), Copper (Cu), Chlorides and Ammonium ions using standard methods. Physical parameters were analyzed in situ whereas chemical parameters were analyzed in the laboratories in Burundi Institute of Agricultural Sciences (ISABU) and University of Burundi. Data were analyzed using R-studio-1.0.153, GenStat 64-bit Release 14.1 and SSPS. Results on the physicochemical parameters indicated that coffee factory effluent has a polluting potential during coffee processing peak. The concentrations of the physicochemical parameters were significantly (p < 0.05) higher downstream (D) compared to upstream (U) of the river water sampling points. All downstream sites had COD, BOD5, TSS and pH values above allowable limits set by WHO and Burundi. The polluting impact of public wet coffee processing factories was significantly higher than that of private and cooperatives owned factories (p < 0.05). Measures should be taken in order to protect water bodies.